Morphological study and conidia production of Beauveria bassiana isolates before and after reisolation in Rhipicephalus microplus - Rodrigues, Caio Junior Balduino Coutinho; de Freitas, Maria Clemente; Perinotto, Wendell Marcelo de Souza; Santos, Fernanda da Silva; de Paulo, Jéssica Fiorotti; Quinelato, Simone; Camargo, Mariana Guedes; Angelo, Isabele da Costa; Bittencourt, Vânia Rita Elias Pinheiro (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Coutinho-Rodrigues C.J.B., de Freitas M.C., Perinotto W.M.deS., Santos F.S., de Paulo J.F., Quinelato S., Camargo M.G., Angelo I.daC. & Bittencourt V.R.E.P. [Morphological study and conidia production of Beauveria bassiana isolates before and after reisolation in Rhipicephalus microplus]. Estudo morfológico de isolados de Beauveria bassiana antes e após reisolamento em Rhipicephalus microplus Revista Brasileira de Medicina Veterinária, 38(supl. 3):54-65, 2016. Departamento de Parasitologia Animal, Anexo 1, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR 465, KM 47, Seropédica, RJ 23890-000, Brasil. E-mail: vaniabit@ufrrj.br Beauveria bassiana is a cosmopolitan arthropod pathogenic fungus that possesses the cattle tick Rhipicephalus microplus as host. In this context, studies involving morphology and production of conidia on culture medium may indicate isolates that have potential for using in wide-scale. The present study evaluated the macro and the micromorphology, in addition to the conidia production of ten B. bassiana isolates before and after one passage (development cycle) on R. microplus. Macroscopically, variations in diameter, surface, texture, exudation and reverse coloration were observed after reisolation. On the other hand, the process did not alter the development of conidiophores, the shape and size of conidia. Regarding the conidiation, six isolates increased the number of conidia counted per area. Highlighting, the isolate Bb 02, which has the tick as the original host, presented an increase of the powdery and conidia production posteriorly of a single passage. Thus, it is believed that for future commercial evaluations, studies involving more passages in potential hosts, as well as their association to pathogenicity and enzymatic activity analyzes, may express more relevant results for biological control.